Caracterização clínico-patológica, microscópica e da densidade vascular em fibroma de células gigantes - Silva, Joyce Natiele Da (2017)
Giant Cell Fibroma (GCF) is considered to be a neoplastic lesion mainly constituted by giant cells, either mono or binucleated, and fusiform and stellate cells. In order to elucidate the biological behavior of GCF, this study aimed to analyze the clinicopathologic and microscopic aspects in hematoxilyn and eosin of 25 GCF cases and the mean vascular density of these same lesions of the Oral Pathology Laboratory collection at the Department of Pathology and Parasitology of the Federal University of Alfenas, using immunohistochemistry using CD34. Regarding clinical data, the results indicated that 68% of GCF cases belonged to females, whilst 86.7% corresponded to white patients. The most frequent age range was 51-60 (31.3%), and 72% of cases were assymptomatic. Statistical analyses revealed tongue and buccal mucosa as the most frequent sites for GCF (32 and 20%, respectively). Microscopically, GCF lesions presented hyperplasic (88%) and parakeratinized (60%) epithelium; 76% and 64% of the lesions contained few cells in the lamina propria and in the sub-epithelial portion, respectively. 44% showed elongated epithelial crests and 72% presented thick fibers spread throughout all the connective tissue. Concerning the amount of blood vessels, 72% of GCF were related to mild or discrete vascularization, and 64% of those vessels were not congested or hyperemic. 60% of GCF showed discrete inflammation and up to 5 giant cells per observed field, being 48% of these cells mononucleated. CD34 immunohistochemistry was conducted in and the medium vascular density (MVD) in a 56 mm2 area in the sub-epithelial region presented a median of 6.84 and a P value of 0.0679 (0.13 microvessels per mm2) and in the deep region 3.67 (P=0.0679 – 0.07 microvessels per mm2). In the subepithelial region the P value was 0.5133 and in the deep region 0.9526, therefore lacking statistically significant differences regarding MVD among lesions and number of vessels in cases with different quantities of giant cells. The clinicopathologic, microscopic and MVD characterizations of GCF should indeed be further explored, as GCF is a neoplastic disease to be considered among other fibrous oral lesions.